Reviews (New blackfriars, 1966)
THE PROTESTANT ESTABLISHMENT by E. Digby Baltzell WE JEWS AND JESUS by Samuel Sandmel. Victor Gollantz Ltd SIMONE WEIL: SEVENTY LETTERS. Translated and arranged by Richard Rees THE SOCIOLOGY OF RELIGION by Max Weber. Methuen A CHRISTIAN PHILOSOPHY OF EXISTENCE THE MOMENT OF TRUTH. MYSTERIUM MORTIS by Ladislaus Boros (translation by Gregory Bainbridge. O.S.B.) TEMOINS DE LA SPIRITUALITE OCCIDEN-TALE by Dom Jean Leclercq THE TEMPTATION AND THE PASSION: THE MARKAN SOTERIOLOGY JESUS CHRIST IN THE OLD TESTAMENT by Anthony Tyrrell Hanson SYNOPSE DES QUATRE EVANGILES by P. Benoit and M-E Boismard Editions du Cerf